2018
DOI: 10.1111/1365-2656.12805
|View full text |Cite
|
Sign up to set email alerts
|

Ecological determinants of avian malaria infections: An integrative analysis at landscape, mosquito and vertebrate community levels

Abstract: Vector and host communities, as well as habitat characteristics, may have important but different impacts on the prevalence, richness and evenness of vector-borne parasites. We investigated the relative importance of (1) the mosquito community composition, (2) the vertebrate community composition and (3) landscape characteristics on the prevalence, richness and evenness of avian Plasmodium. We hypothesized that parasite prevalence will be more affected by vector-related parameters, while host parameters should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 114 publications
1
90
4
2
Order By: Relevance
“…Distance to water sources was an important predictor of malaria distributions in both Porto Santo and Tenerife (González‐Quevedo et al, ). Due to the aquatic larval development of mosquitoes, higher vector abundance and malaria are found in proximity to water (Ferraguti et al, ; Ganser et al, ; Illera et al, ). In the present study, distance to urban areas was removed prior to model selection due to a positive collinearity with distance to water sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distance to water sources was an important predictor of malaria distributions in both Porto Santo and Tenerife (González‐Quevedo et al, ). Due to the aquatic larval development of mosquitoes, higher vector abundance and malaria are found in proximity to water (Ferraguti et al, ; Ganser et al, ; Illera et al, ). In the present study, distance to urban areas was removed prior to model selection due to a positive collinearity with distance to water sources.…”
Section: Discussionmentioning
confidence: 99%
“…We modeled the environmental predictors of malaria distributions in Porto Santo to understand fine-scale spatial differences in malaria TA B L E 9 Summary of linear models of the association between genetic variants and malaria risk in Berthelot's pipits on Porto Santo (PS) and Tenerife (TF) higher vector abundance and malaria are found in proximity to water (Ferraguti et al, 2018;Ganser et al, 2016;Illera et al, 2017).…”
Section: Environmental Predictors Of Malaria Riskmentioning
confidence: 99%
“…Differences on parasite infections may be due to a variety of other factors, including the phylogeny of birds [ 32 , 70 , 71 ], avian community composition [ 67 , 72 ], bird species [ 14 ], food availability, altitude or woodland edge [ 30 , 73 ], microhabitat [ 74 ] or landscape characteristics [ 75 ]. As observed in other studies, we observed marked differences in infection status depending on bird species, a factor that explained most of the infection variability in our models.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies argue that the dilution effect is actually idiosyncratic, existing only under specific circumstances (Wood et al, 2014;Young et al, 2013). Rigorously assessing the diversity-disease relationship is crucial for better predicting disease dynamics giving the ongoing host range shifts, local extinction events and global biodiversity decline (Ferraguti et al, 2018;Huang et al, 2016;Johnson, De Roode, et al, 2015;Johnson, Ostfeld, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%